2009
DOI: 10.1021/ac9011254
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Biosensing Using Amplification-by-Polymerization

Abstract: A novel signal amplification strategy for electrochemical detection of DNA and proteins based on the amplification-by-polymerization concept is described. Specifically, a controlled radical polymerization reaction is triggered after the capture of target molecules on the electrode surface. Growth of long chain polymeric materials provides numerous sites for subsequent aminoferrocene coupling, which in turn significantly enhances electrochemical signal output. Activators generated electron transfer for atom tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 31 publications
(50 reference statements)
1
92
0
Order By: Relevance
“…For example, Fc-based polymer brushes grafted on solid substrates have been employed for the development of electro-active and electro-catalytic films, electrochemical DNA sensors, and amperometric biosensors [50][51][52][53]. Fu et al reported a gold substrate with surface-grafted Fc-based polymer brushes (Au-g-PFTMA) (P24), which was prepared by combination of surface-initiated atom transfer radical polymerization (SI-ATRP) and CuAAC in one pot (Scheme 6) [54].…”
Section: Click Modification Of Functional Polymeric Surfacesmentioning
confidence: 99%
“…For example, Fc-based polymer brushes grafted on solid substrates have been employed for the development of electro-active and electro-catalytic films, electrochemical DNA sensors, and amperometric biosensors [50][51][52][53]. Fu et al reported a gold substrate with surface-grafted Fc-based polymer brushes (Au-g-PFTMA) (P24), which was prepared by combination of surface-initiated atom transfer radical polymerization (SI-ATRP) and CuAAC in one pot (Scheme 6) [54].…”
Section: Click Modification Of Functional Polymeric Surfacesmentioning
confidence: 99%
“…Ferrocene-based polymers have wide applications in different fields like optical display technologies [17], amperometric biosensors [18,19], DNA and protein sensors [20,21], carbon monoxide sensors, [22] and in the construction of optical logic gates [23]. Additionally, ferrocene-based photocross-linkable redox polymers have been synthesized for the design of enzyme-based sensors and fuel cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) technology has been used for the amplification and detection of trace amounts of DNA (5). This technology can theoretically detect single stranded DNA and has good specificity (6).…”
Section: Introductionmentioning
confidence: 99%